Analisis Kritis Ibn Taymiyyah Terhadap Amalan Dhikr `Ism al-Dhat: Satu Ulasan dan Komentar - Syed Omar, Syed Hadzrullathfi; Sa’ari, Che Zarrina; Engku Wok, Engku Ibrahim (Jurnal Usuluddin, 2009)
This article discusses about the critical view of Ibn Taymiyyah on the Sufi practice of dhikr Ism al-Dhat as a way of remembrance of Allah S.W.T. Based on the evidence and arguments that held by him, he judges the practice as a bid`ah which is regarded as makruh. In addition, this article also presents answers on the views of Ibn Taymiyyah based on the opinion of prominent Sufis figures in order to argue the validity of the practice of dhikr Ism al-Dhat.